A Short Review On Modification And Characterization Of Heat Moisture Treated Starch From Banana (Musa Spp.) - PPTI, Pusat Pengajian Teknologi Industri (Universiti Sains Malaysia, 2021)
Food waste generated from banana is significance due to its short life span and delicate condition as it ripen. The problem can be reduced by transforming the banana into flour and further treated with heat moisture treatment (HMT) to increase its functionality. In this review, modification of banana flour (ripe and unripe) with HMT (30% moisture, 100-121°C, 1-24 h) and the physico-chemical properties and resistant starch content of modified banana flour will be discussed. HMT has been found to able modifying plant starch due to the rearrangement of starch molecule which causes changes to the properties of starch. From the review, resistant starch has been found up to 84% after HMT modification. HMT also reduce swelling power and solubility of banana starch. However, X-ray diffraction and FTIR shows no changes after HMT. HMT able to increase the functionality of banana starch as it produced resistant starch type 3, which more stable for food processing.